PENINGKATAN KAPASITAS KADER JPPA KELURAHAN TANJUNGMAS MELALUI PELATIHAN KONSELING DENGAN METODE CCT - Tsaniatus Solihah; Endang Widyorini; Daniswara A. Wijaya (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Domestic Violence (KDRT) remains a serious problem that significantly impacts the psychological condition of women and children, thus requiring empathetic psychosocial assistance with a victim perspective at the community level. This community service activity aims to improve the knowledge and skills of the Women and Children Protection Network (JPPA) cadres in Tanjungmas Village through counseling training with a client-centered therapy (CCT) approach. The implementation method includes Focus Group Discussions (FGDs) and two-day training with interactive lectures, discussions, case studies, and practical simulations. Evaluation is carried out through participant reaction evaluation, learning evaluation using pre-tests and post-tests, and skill evaluation through observation of counseling practices, with analysis of knowledge increases using the Wilcoxon Signed Ranks Test. The results of the activity showed that participants responded positively to the training implementation, there was a significant increase in participant knowledge (p < 0.05), and most participants were able to apply basic counseling skills such as building rapport, empathy, and active listening, although reflection skills still need to be strengthened. Client-centered therapy-based counseling training has proven effective in increasing the capacity of JPPA cadres and is expected to strengthen the quality of psychosocial support for victims of domestic violence at the community level in a sustainable manner.